Physical mapping of a pollen modifier locus controlling self-incompatibility in apricot and synteny analysis within the Rosaceae - Zuriaga, Elena; Molina, Laura; Badenes, María L.; Romero, Carlos (2017)
S-locus products (S-RNase and F-box proteins) are essential for the gametophytic self-incompatibility (GSI) specific recognition in Prunus. However, accumulated genetic evidence suggests that other S-locus unlinked factors are also required for GSI. For instance, GSI breakdown was associated with a pollen-part mutation unlinked to the S-locus in the apricot (Prunus armeniaca L.) cv. ‘Canino’. Fine-mapping of this mutated modifier gene (M-locus) and the synteny analysis of the M-locus within the Rosaceae are here reported. A segregation distortion loci mapping strategy, based on a selectively genotyped population, was used to map the M-locus. In addition, a bacterial artificial chromosome (BAC) contig was constructed for this region using overlapping oligonucleotides probes, and BAC-end sequences (BES) were blasted against Rosaceae genomes to perform micro-synteny analysis. The M-locus was mapped to the distal part of chr.3 flanked by two SSR markers within an interval of 1.8 cM corresponding to ~364 Kb in the peach (Prunus persica L. Batsch) genome. In the integrated genetic-physical map of this region, BES were mapped against the peach scaffold_3 and BACs were anchored to the apricot map. Micro-syntenic blocks were detected in apple (Malus × domestica Borkh.) LG17/9 and strawberry (Fragaria vesca L.) FG6 chromosomes. The M-locus fine-scale mapping provides a solid basis for self-compatibility marker-assisted selection and for positional cloning of the underlying gene, a necessary goal to elucidate the pollen rejection mechanism in Prunus. In a wider context, the syntenic regions identified in peach, apple and strawberry might be useful to interpret GSI evolution in Rosaceae.